Determinants Of Islamic Bank Financing During Economic Turbulence - Selian, Mardiah Mutiara Puspitasari; Lutfi, Lutfi (LPPM ISNJ Bengkalis, 2024)
The Covid-19 outbreak has caused turbulence in Indonesia's economic growth, thereby disrupting the performance of Islamic banks, especially in the distribution of financing. This research examines the influence of economic turbulence, third-party deposits, bank size, capital and profitability on financing disbursed by Islamic banks in Indonesia. The population of this research is Islamic commercial banks in Indonesia in the 2017-2022 period. The sample selection used a purposive sampling method and obtained ten Islamic banks. The data analysis technique uses panel data analysis with a fixed effect model. The research results prove that third-party deposits positively and significantly impact financing, while bank size and capital negatively and significantly impact financing. However, economic turbulence and profitability do not affect financing. When financing is divided based on contracts, economic turbulence negatively impacts profit-sharing-based financing, and profitability negatively impacts receivables-based financing. These findings can be a reference for Islamic banks to maintain the availability of third-party deposit funds to support financing expansion and further optimize their capital by channelling it to more productive assets in the form of financing. These findings can complement existing theories and support the business cycle theory that Islamic banks tighten financing based on profit sharing, which carries higher risks.